2015
DOI: 10.1007/s11356-015-5647-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of Scots pine to climatic factors on reclaimed oil shale mined land

Abstract: Afforestation on reclaimed mining areas has high ecological and economic importance. However, ecosystems established on post-mining substrate can become vulnerable due to climate variability. We used tree-ring data and dendrochronological techniques to study the relationship between climate variables and annual growth of Scots pine (Pinus sylvestris L.) growing on reclaimed open cast oil shale mining areas in Northeast Estonia. Chronologies for trees of different age classes (50, 40, 30) were developed. Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Faster growth was primarily caused by higher air temperatures in the winter and in the period from May to August, but definitely to a lesser extent, which was also partially proven in central and eastern Poland. In Estonia, in the reclaimed area after open-cast shale mining, it was shown that spring air temperatures contributed to the radial growth of Scots pine, while above average air temperatures occurred in the summer months to the inhibition of wood production [53].…”
Section: Discussionmentioning
confidence: 99%
“…Faster growth was primarily caused by higher air temperatures in the winter and in the period from May to August, but definitely to a lesser extent, which was also partially proven in central and eastern Poland. In Estonia, in the reclaimed area after open-cast shale mining, it was shown that spring air temperatures contributed to the radial growth of Scots pine, while above average air temperatures occurred in the summer months to the inhibition of wood production [53].…”
Section: Discussionmentioning
confidence: 99%
“…Tree-ring data are useful for exploring the effects of soil moisture status and several other factors on tree and forest growth. High-frequency signals extracted from tree-ring series can be utilized to address relationships with short-term climatic variability, and a number of studies have identified links between temperature and precipitation on tree radial growth at an annual scale using ring-width data of various tree species in Estonia [14][15][16][17][18] and other countries in the Baltic region [19][20][21][22]. Low-frequency signals contained in ring-width series can be associated with tree size or age and various endogenous and exogenous disturbances [23].…”
Section: Introductionmentioning
confidence: 99%
“…Technical reclamation involves heavy interventions such as the restructuring of landforms, importing soil, and planting or sowing of plants. The target ecosystem may not always be the original ecosystem lost by mining or industrial activities, but a system that is considered useful for some purpose (SER 2004), for example forest management (Metslaid et al 2015). Intermediate interventions are called assisted restoration and may include an ecologically justified enhancement of abiotic site conditions, the suppression of undesirable species, planting or sowing target species, and creating microsite heterogeneity.…”
Section: Ecological Restoration and Reclamationmentioning
confidence: 99%
“…In the papers of this issue, attention is given to passive restoration and the factors influencing spontaneous succession (e.g., Nikolic et al 2015;Tropek et al 2015;Horáčková et al 2015;Alday et al 2015), to field experiments comparing ecological restoration measures (Tarvainen and Tolvanen 2015;Karofeld et al 2015), to the comparison between reclamation and passive restoration (Řehounková et al 2016; Šebelíková et al 2015), and to the reclamation by afforestation (Metslaid et al 2015). Based on the results, passive restoration seems to be an effective approach at many post-mining and postindustrial sites (but see Kopeć et al 2015), whereas technical reclamation may have negative effects on the biodiversity, since it decreases the amount of habitats for specialized threatened species (Tropek et al 2015;Řehounková et al 2016) or maintains the pool of seeded alien species that may spread to the surrounding environment (Rydgren et al 2015).…”
Section: Ecological Restoration and Reclamationmentioning
confidence: 99%
See 1 more Smart Citation